Mitochondrial Dysfunction in Diabetic Periodontitis: Mechanisms and Therapeutic Potential - Meng L; Wen W (Journal of Inflammation Research)
Leilei Meng,1,2 Wenjie Wen1 1Anhui Province Engineering Research Center for Dental Materials and Application, School of Stomatology, Wannan Medical College, Wuhu, 241002, People’s Republic of China; 2Department of Pathophysiology, Anhui Medical University, Hefei, 230000, People’s Republic of ChinaCorrespondence: Wenjie Wen, Email 20230025@wnmc.edu.cnAbstract: Diabetic periodontitis is a common oral complication of diabetes characterized by progressive destruction of periodontal tissues. Recent evidence suggests that mitochondrial dysfunction plays a crucial role in the pathogenesis and progression of this condition. This review aims to systematically summarize the role and potential mechanisms of mitochondrial dysfunction in diabetic periodontitis. We first explore the relationship between diabetes and mitochondrial dysfunction, then analyze the specific manifestations of mitochondrial dysfunction in diabetic periodontitis, including morphological changes, energy metabolism disorders, increased oxidative stress, and enhanced apoptosis. We further delve into the connections between mitochondrial dysfunction and the pathogenic mechanisms of diabetic periodontitis, such as exacerbated inflammatory responses, decreased tissue repair capacity, and autophagy dysregulation. Finally, we discuss potential therapeutic targets based on mitochondrial function, including antioxidant strategies, mitochondria-targeted drugs, and autophagy regulators. We also propose future research directions, emphasizing the need for in-depth exploration of molecular mechanisms, development of new diagnostic markers and therapeutic strategies, and personalized treatment approaches. This review provides new insights into understanding the pathogenic mechanisms of diabetic periodontitis and offers a theoretical basis for developing targeted prevention and treatment strategies to improve oral health in diabetic patients.Keywords: diabetic periodontitis, mitochondrial dysfunction, inflammation, therapeutic targets